1999
DOI: 10.1034/j.1399-3003.1999.14b03.x
|View full text |Cite
|
Sign up to set email alerts
|

Different cytokine profiles in cryptogenic fibrosing alveolitis and fibrosing alveolitis associated with systemic sclerosis A quantitative study of open lung biopsies

Abstract: Different cytokine profiles in cryptogenic fibrosing alveolitis and fibrosing alveolitis associated with systemic sclerosis: a quantitative study of open lung biopsies. S. Majumdar, D. Li, T. Ansari, P. Pantelidis, C.M. Black, M. Gizycki, R.M. du Bois, P.K. Jeffery. ERS Journals Ltd 1999. ABSTRACT: Differences in the inflammatory response and prognosis of cryptogenic fibrosing alveolitis (CFA) and that associated with systemic sclerosis (FASSc) are beginning to emerge. It is hypothesized that these differences… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
47
1
1

Year Published

1999
1999
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(54 citation statements)
references
References 34 publications
5
47
1
1
Order By: Relevance
“…Previous studies in IPF and sarcoid have shown that while IL-4 and IFN-␥ are coexpressed in sarcoid, IFN-␥ expression is reduced or absent in IPF allowing IL-4 expression to dominate (14,19). The results of the present study suggest that these conditions favor the increased expression of IGF-I by macrophages, a condition that is seen in lung biopsy specimens obtained from IPF patients (12).…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Previous studies in IPF and sarcoid have shown that while IL-4 and IFN-␥ are coexpressed in sarcoid, IFN-␥ expression is reduced or absent in IPF allowing IL-4 expression to dominate (14,19). The results of the present study suggest that these conditions favor the increased expression of IGF-I by macrophages, a condition that is seen in lung biopsy specimens obtained from IPF patients (12).…”
Section: Discussionsupporting
confidence: 66%
“…Animal model studies of interstitial fibrosis using bleomycin, silica, and thoracic irradiation support these conclusions (16 -18). In contrast, expression of the Th1 cytokine, IFN-␥, has been found to be reduced or absent in IPF yet is prominent in granulomatous lung disorders such as sarcoid (13,19,20). These findings are consistent with previous observations that IFN-␥ 1) inhibits IGF-I production by macrophages (21), 2) inhibits collagen synthesis by fibroblasts (22), 3) is efficacious in ameliorating pulmonary fibrosis in the bleomycin model in mice (23), and 4) modestly improves pulmonary function and survival in IPF patients (24).…”
mentioning
confidence: 99%
“…Idiopathic pulmonary fibrosis, for example, results from Th2-mediated inflammation, leading to progressive deposition of extracellular matrix, pulmonary fibrosis, and destruction of pulmonary parenchyma (1)(2)(3). In radiotherapy of thoracic malignancies, the Th2 response can cause pneumonitis and subsequent pulmonary fibrosis, limiting the dose of radiation (4).…”
Section: Global Gene Expression Profiles Duringmentioning
confidence: 99%
“…There are many causes of pulmonary fibrosis, including exposure to fibrosis-inducing agents such as silica (4) and coal dust (5). Pulmonary fibrosis is also a feature found in disorders such as scleroderma (6), sarcoidosis (7), and cystic fibrosis (8). Idiopathic pulmonary fibrosis (IPF) 3 is a particularly deadly form of pulmonary fibrosis with unknown causes (2).…”
mentioning
confidence: 99%